La mirada transgenérica - Judith Halberstam (Universitat de Barcelona, 2004)
This text studies the construction and development of the transgender look in contemporary queer cinema, specifically: The Crying Game (Neil Jordan, 1992), Boys don't Cry (Kimberly Peirce, 2000) and By Hook or by Crook (Harry Dodge and Silas Howard, 2001). The analysis examines carefully the constitution of a meaningful materiality of the body through the gaze and the dialogue-confrontation between the transgender look and mainstream cinema's gaze, in its capability to regulate pleasures and sexual identities.